Analisis validation for fat content measurement by extractor and soxhlet methods with variation in the purity of the N-hexane solvent - Nugraha Yuwana (Labor Dasar dan Sentral Universitas Andalas, 2021)
Generally, the determination of fat content in food is based on the SNI 01-2891-1992 method. But, the JP Selecta extractor can also be used for fat content analysis in a shorter time. The use of two different types of equipment without cross-examination may give a different result. The use of solvents with different purity also triggers differences in test results. This research had been aimed to determine the comparison of fat content with different test methods and balance the two test results with the most optimal extraction results as a reference. This research used a completely randomized design (CRD) with 2 types of factors, namely the test method (soxhlet and extractor) and the solvent purity (technical, distillate, and pro-analysis). Based on the analysis of variance, variations in solvent purity and different types of test equipment / methods had a significant effect on fat content. Pro-analyst solvent was preferred for fat content analysis because the purity reaches 99%. The equalization of the fat test results was done by changing the extraction time on JP Selecta to 2 hours 20 minutes, untill the analysis of variance results on the two methods showed an unsignificant effect or were considered equivalent.